Compressive Strength of Alginate Impression Material Incorporated with Silver and Zirconium Oxide Nanoparticles - Luma Mudhafar Al-Nema; Ahmed Asim Al-Ali (University of Mosul, College of Dentistry, 2023)
Aims: To investigate the effect of adding nanoparticles on the compressive strength of alginate impression material. Materials and Methods: In this study, two types of nanoparticles were added to alginate impression materials: silver and zirconium oxide at four concentrations: 0.5 %, 1%, 2%, and 5% by weight. Compressive strength was tested for 45 samples made according to American Dental specification no.18 for the alginate impression material. Results: The addition of silver nanoparticles did not alter the compressive strength of alginate impression material, whereas the addition of zirconium oxide significantly decreased its compressive strength. Conclusions: The incorporation of silver nanoparticles into alginate impression materials as antimicrobial agents had no negative effect on its compressive strength, whereas adding antimicrobial zirconium oxide nanoparticles significantly reduced the compressive strength of alginate impression material